Performance based earthquake engineering assessment of a self-centering, post-tensioned concrete bridge system. - Lee, Won K.
Highway bridges in highly seismic regions can sustain considerable residual displacements in their columns following large earthquakes. These residual displacements are an important measure of post-earthquake functionality, and often determine whether or not a bridge remains usable following an earthquake. In this study, a self-centering system is considered that makes use of unbonded, post-tensioned steel tendons to provide a restoring force to bridge columns to mitigate the problem of residual displacements. To evaluate the proposed system, a code-conforming, case-study bridge structure is analyzed both with conventional reinforced concrete columns and with self-centering, post-tensioned columns using a formalized performance based earthquake engineering (PBEE) framework. The PBEE analysis allows for a quantitative comparison of the relative performance of the two systems in terms of engineering parameters such as peak drift ratio as well as more readily understood metrics such as expected repair of costs and downtime. The self-centering column system is found to undergo similar peak displacements to the conventional system, but sustains lower residual displacements under large earthquakes, resulting in similar expected repair costs but significantly lower expected downtimes.
Keywords: Residual displacements; Performance-based earthquake engineering; Post-tensioned concrete; Self-centering.; Highway structures